2009
DOI: 10.1111/j.1365-2125.2009.03426.x
|View full text |Cite
|
Sign up to set email alerts
|

Medication errors: pharmacovigilance centres in detection and prevention

Abstract: 1. Detecting medication errors needs collaboration between various organizations, such as patient safety institutions, pharmacovigilance centres, and poison control centres. In order to evaluate the input of pharmacovigilance centres and poison control centres in detecting and evaluating medication errors a pilot project was initiated by the World Alliance for Patient Safety in collaboration with the Uppsala Monitoring Centre; the Moroccan pharmacovigilance centre acted as project coordinator. As part of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 6 publications
1
30
0
Order By: Relevance
“…It is important to manage, using national statistics, the percentage of therapeutic ineffectiveness and medication errors. A study conducted in Morocco found that PV centers can contribute to the detection and prevention of medication errors . As therapeutic ineffectiveness—unexpected or unexplained—is hypothetically an important reportable event in PV, observations of unexpected ineffectiveness in patients can provide crucial information …”
Section: Discussionmentioning
confidence: 99%
“…It is important to manage, using national statistics, the percentage of therapeutic ineffectiveness and medication errors. A study conducted in Morocco found that PV centers can contribute to the detection and prevention of medication errors . As therapeutic ineffectiveness—unexpected or unexplained—is hypothetically an important reportable event in PV, observations of unexpected ineffectiveness in patients can provide crucial information …”
Section: Discussionmentioning
confidence: 99%
“…Toxic effects due to oral administration to children in the first week of life of uterotonic ergot alkaloid had been documented in only two previous reports: a case of poisoning observed in Italy in 1985; a review of 34 cases of oral exposure handled by the Belgian Poison Control Centre between 1969 and 1999, including 9 children aged <1 month presenting with low severity effects and a 15‐day‐old female baby who developed severe clinical toxicity . In 2009, a retrospective analysis of the Moroccan Pharmacovigilance Centre database highlighted that one of the most frequent medication errors occurring in that country was administration of methylergometrine maleate to the wrong patients, mainly due to confusing prescription …”
Section: Discussionmentioning
confidence: 99%
“…Simpler and cheaper methods are available and should be widely implemented. For example, error reporting is important in both detection and prevention [7], and pharmacovigilance has a role to play [13]. However, chief among the preventive methods is education [14].…”
Section: Detection and Preventionmentioning
confidence: 99%